Molecular dynamics study-based mechanism of nefiracetam-induced NMDA receptor potentiation. (April 2015) - Omotuyi, Olaposi I.; Ueda, Hiroshi
Graphical abstract: Highlights: Nefiracetam-induced N -methyl-d -aspartic acid (NMDA) receptor signaling was investigated. Nefiracetam-induces NMDA receptor ligand binding domain conformation which favors glycine dissociation. Nefiracetam replaces glycine within glycine-binding pocket upon dissociation. The modulatory effect of nefiracetam on NMDA receptor intra-subunit communication and gating properties are discussed. Abstract: Plastic changes in the brain required for memory formation and long-term learning are dependent on N -methyl-d -aspartic acid (NMDA) receptor signaling. Nefiracetam reportedly boosts NMDA receptor functions as a basis for its nootropic properties. Previous studies suggest that nefiracetam potentiates the NMDA receptor activation, as a more potent co-agonist for glycine binding site than glycine, though the underlying mechanisms remain elusive. Here, using BSP-SLIM method, a novel binding site within the core of spiral β-strands-1-5 of LBD-GLUN1 has been predicted in glycine-bound GLUN1 conformation in addition to the glycine pocket in Apo-GLUN1. Within the core of spiral β-strands-1-5 of LBD-GLUN1 pocket, all-atom molecular dynamics simulation revealed that nefiracetam disrupts Arg523-glycine-Asp732 interaction resulting in open GLUN1 conformation and ultimate diffusion of glycine out of the clamshell cleft. Open GLUN1 conformation coerces other intra-chain domains and proximal inter-chain domains to sample inactivate conformations resulting in closure of the transmembrane gate via a novel gauche trap on threonine 647 (chi-1 dihedral ( χ 1 ) = −45° instead of +45°). Docking of nefiracetam into the glycine pocket reversed the gauche trap and meditates partial opening of the TMD gate within a time-scale of 100 ns as observed in glycine-only state. All these results suggest that nefiracetam can favorably complete with glycine for GLUN1-LBD in a two-step process, first by binding to a novel site of GLUN1-LBD-NMDA receptor followed by disruption of glycine-binding dynamics then replacing glycine in the GLUN1-LBD cleft.